Healthcare Access - Regional Overviews [Working Title] 2019
DOI: 10.5772/intechopen.88982
|View full text |Cite
|
Sign up to set email alerts
|

Access to Maternal Healthcare Services under the National Health Insurance Policy in the Upper West Region, Ghana

Abstract: Health insurance coverage provides the spring board for pregnant women to access and utilise maternal healthcare services. Yet, studies on health insurance coverage, access and utilisation of maternal healthcare are a handful. Consequently, this study examines women's access and utilisation of maternal healthcare services under the free maternal health policy in two districts in northern Ghana. The study adopted the mixed research approach with the aid of the cross-sectional design involving 212 respondents. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Studies conducted at various country levels in SSA have shown that health insurance improves ANC attendance 17 , skilled delivery 18 , 19 and PNC among women of reproductive age. 1 , 20 There is, however, a paucity of empirical literature at the subregional level on the influence of health insurance coverage on maternal healthcare utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted at various country levels in SSA have shown that health insurance improves ANC attendance 17 , skilled delivery 18 , 19 and PNC among women of reproductive age. 1 , 20 There is, however, a paucity of empirical literature at the subregional level on the influence of health insurance coverage on maternal healthcare utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several other studies have found that the health insurance coverage increased the probability of having the recommended number of prenatal visits [19][20][21]. Studies in countries like Ghana, Indonesia, and Rwanda, have found a significant positive impact of health insurance on maternal health outcomes [22,23].…”
Section: Health Care Financing and Maternal Healthmentioning
confidence: 75%
“…But the role of health financing has been a challenging one to examine. It is a well-accepted fact now that health health insurance plays a significant role in improving the financial protection and utilization of maternal healthcare system [16][17][18][22][23][24]26,[44][45][46]. But studying it in maternal health outcomes is challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several other studies have found that the health insurance coverage increased the probability of having the recommended number of prenatal visits [1921]. Studies in countries like Ghana, Indonesia, and Rwanda, have found a significant positive impact of health insurance on maternal health outcomes [22,23]. Health insurance coverage lowers the risk of maternal deaths due to adequate health care financing.…”
Section: Introductionmentioning
confidence: 83%